STUDYING OF DRYING CONDITION IMPACT ON GINSENG TISSUE CULTURE BIOMASS QUALITY INDICATOR - N. I. Laevskaia; Y. S. Selyutina; I. Ye. Kaukhova; N. S. Pivovarova (Разработка и регистрация лекарственных средств)
At the moment the task of obtaining high-efficient plant medicinal with wide range of action to be used for pharmaceutical, cosmetic, food industry as a biologically active additives remains valid. The ginseng tissue culture drying parameters impact on the biomass quality (chemistry of biologically active substances and antioxidant activity) is studied in this article. It was identified that increasing temperature and decrease the drying time of ginseng tissue increases antioxidant activity. Qualitative and quantitative analyses confirmed authenticity of the biomass compared to the control (ginseng root tincture).